Self-Regulated Learning Siswa SMA dalam Mengikuti Pembelajaran Daring - Uke Khairunnisa (Jurnal Halaqah, 2022)
The Covid-19 pandemic has changed the learning system in various countries. Online learning policies are referred to as alternative learning that can be done at this time. Self-regulated learning is a skill to manage yourself in an ongoing learning process. Researchers used a literature review design to explain the purpose of writing articles, namely: (1) obtaining a picture of high school students' self-regulated learning in doing online learning in Indonesia; (2) describe effective self-regulated learning strategies in online learning. The results show that high school students in Indonesia have a good level of independent learning which can be seen from the attitude of responsibility, discipline, and have high initiative and motivation to learn. In this literature study we identified seven self-regulated learning strategies related to academic achievement in online learning: self-efficacy, metacognition, time management, effort regulation, critical thinking, elaboration, and help-seeking.